The Effect of Operating Leverage, Cyclicality, and Firm Size on Business Risk - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
This research has two objectives. The first objective is to analyze whether the beta of unleverage firms significantly reflects the sensitivity of a stock's returns to changes in returns on the market portfolio. The second one is to analyze the impact of the operating leverage, cyclicality, and firm size to the business risk. The study was carried out on the 30 most active manufacturing companies in the Jakarta Stock Exchange, based on trading frequency during 1993-1995 period. The first objective was analyzed by using the market model and time series linear regression. The beta is measured by the coefficient of the regression, where the dependent variable is returns on a stock and the independent variable is returns on market portfolio. The result shows that most betas are statistically significant. Thus, the beta of unleve rage firms can be a proxy to the business risk. The second objective is analyzed by using cross sectional linear regression. The result of the partial test indicates that the variables of the cyclicality and firm size have significant effect on the business risk, but the operating leverage does not. The result on the simultaneous test also indicates that the cyclicality and firm size have significant effect to the business risk. The cyclicality has positive impacts on the business risk, while the firm size has negative impacts on the business risk. Keywords: business